The effectiveness of the concept ERAS (Enhanced Recovery After Surgery) in patients of surgical intensive care unit - Jana Richtarova; Eva Mrazkova; Igor Satinsky (Global Journal of Perioperative Medicine - Peertechz Publications, 2020)
Introduction: The objective of the survey study is to the accessible world literature sources and comparative studies dealing with the effectivity of the ERAS concept in the patients after the surgical interventions in the surgical emergency units and to present adoption of concept in the Czech Republic. Method: For searching of the needed information and data they were used the literature sources and comparative studies from the open access and licensed database sources (Scopus, SpringerLink, Medline Complete, ScienceDirect, Web of Science, ProQuest, EBSCOhost, Wiley Online Library). The conclusions of the concrete comparative studies dealing with the conceptual effectivity of the perioperative care ERAS were analysed. On the analytical base of the gained information drawing from the accessible literature and from 8 quantitative studies published in the years 2009-2013. Results: It is clear that following of the ERAS protocol principle in the surgical workplaces in the Czech Republic is adopted only in the limitation of the routine application of the nasogastric probe, application of epidural analgesia and parenteral preoperative nutritional support if enteral not possible. Conclusion: The positive effect of the new way of the perioperative care, ERAS is proved as for the qualitative improvement of the treatment and nursing process, as for decreasing of the postoperative complications and shortening of the hospitalization period including decreasing of the economic expenditures connected to the treatment and hospitalization of the surgical patients. In comparison with established ERAS protocol, in the Czech Republic the principles are put into effect less significantly. The mentioned experiences and results can be the useful source for the next surgical workplaces.